Implementasi Prinsip Fleksibilitas Pengelolaan Dana Badan Layanan Umum Daerah pada Instansi Pemerintah - Alicia Caecariaz Khoirullisa; Antonia Nataya Pringgosari; Intan Rahmawati (Jurnal Pengabdian Dian Mandala, 2023)
This research aims to determine the extent and quality of the implementation of flexibility principles in government agencies regarding the management of BLUD funds. The research method employed is qualitative with descriptive analysis. Data sources for this study consist of secondary data obtained from literature reviews, documentation, and scholarly journals, as well as primary data acquired through interviews and observations. The research findings reveal that the implementation of flexibility principles in managing BLUD within government agencies has been conducted effectively by providing transparent information to the public and adhering to the principles of accountability, responsibility, and independence.